“WRITING MADE EASY”: INTRODUCING KEYS TO SUCCESSFUL ACADEMIC WRITING TO STUDENTS OF ENGLISH EDUCATION - Adaninggar Septi Subekti; Lemmuela Alvita Kurniawati (Jurnal Abdimas Bina Bangsa, 2023)
This community service activity was conducted in the form of a public lecture on keys to successful academic writing with the English Language Education Study Programme of Universitas Kristen Indonesia (UKI) Toraja being the partner of the community service programme. The public lecture was conducted on-site at the main hall of UKI Toraja Campus 1, lasted for a total of three hours and was attended by 191 students and several lecturers. Among the key contents of the lecture was the reminder to ensure that each paragraph only contains one main idea and to resist the desire to put too many ideas in one paragraph. Furthermore, the lecture also introduced the concept of sandwich paragraph structure and several Artificial Intelligence (AI) tools to help the participants organise their writing. From the online questionnaire distributed at the end of the session, it was found that the duration of their study did not significantly impact their foreign/second language (L2) writing proficiency. Despite the possible limitations, the community service activity was a success and some aspects to improve are identified for the improved quality of future programmes